Introduction to criminal justice - Roberson, Cliff (Copperhouse Pub. Co., 2000)
This introductory core text will lead your student to an understanding of the evolution of the criminal justice system through the modern-day workings of police agencies, the court process, and correctional institutions. All elements are thoroughly covered in a straightforward, reader-friendly format. Thought-provoking, practical discussion questions at the end of each chapter enhance comprehension